Antiviral effect of high-dose ivermectin in adults with COVID-19: A proof-of-concept randomized trial. (July 2021) - Krolewiecki, Alejandro; Lifschitz, Adrián; Moragas, Matías; Travacio, Marina; Valentini, Ricardo; Alonso, Daniel F.; Solari, Rubén; Tinelli, Marcelo A.; Cimino, Rubén O.; Álvarez, Luis; Fleitas, Pedro E.; Ceballos, Laura; et al.
Abstract: Background: There are limited antiviral options for the treatment of patients with COVID-19. Ivermectin (IVM), a macrocyclic lactone with a wide anti-parasitary spectrum, has shown potent activity against SARS-CoV-2 in vitro . This study aimed at assessing the antiviral effect of IVM on viral load of respiratory secretions and its relationship with drug concentrations in plasma. Methods: Proof-of-concept, pilot, randomized, controlled, outcome-assessor blinded trial to evaluate antiviral activity of high-dose IVM in 45 COVID-19 hospitalized patients randomized in a 2:1 ratio to standard of care plus oral IVM at 0·6 mg/kg/day for 5 days versus standard of care in 4 hospitals in Argentina. Eligible patients were adults with RT-PCR confirmed SARS-CoV-2 infection within 5 days of symptoms onset. The primary endpoint was the difference in viral load in respiratory secretions between baseline and day-5, by quantitative RT-PCR. Concentrations of IVM in plasma were measured. Study registered at ClinicalTrials.gov: NCT04381884. Findings: 45 participants were recruited (30 to IVM and 15 controls) between May 18 and September 9, 2020. There was no difference in viral load reduction between groups but a significant difference was found in patients with higher median plasma IVM levels (72% IQR 59–77) versus untreated controls (42% IQR 31–73) ( p = 0·004). Mean ivermectin plasma concentration levels correlated with viral decay rate (r: 0·47, p = 0·02). Adverse events were similar between groups. No differences in clinical evolution at day-7 and day-30 between groups were observed. Interpretation: A concentration dependent antiviral activity of oral high-dose IVM was identified at a dosing regimen that was well tolerated. Large trials with clinical endpoints are necessary to determine the clinical utility of IVM in COVID-19. Funding: This work was supported by grant IP-COVID-19-625, Agencia Nacional de Promoción de la Investigación, el Desarrollo Tecnológico y la Innovación, Argentina and Laboratorio ELEA/Phoenix, Argentina.